(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the relationship between leg muscle strength and balance to shooting accuracy in futsal extracurricular participants at MAN Kota Tegal. The problem begins with the low shooting accuracy, which is thought to be caused by weak leg muscle strength and player body balance. The research method used is quantitative correlation. The sample in this study amounted to 30 students who were members of the futsal extracurricular, using the total sampling technique. The research instruments included a vertical jump test for leg muscles, a standing stork test for balance, and a shooting test into the goal. The results of the analysis show that there is a significant relationship between leg muscle strength and balance on shooting accuracy. The t-test showed significant values for both variables, and the F test showed a simultaneous effect that was also significant (p < 0.05). In conclusion, leg muscle strength and balance together affect shooting accuracy. Therefore, futsal training programs need to focus on improving these two aspects to support optimal shooting performance.